A Scarlet Pansy - Scully, Robert, active 1932-1952 (Book collections on Project MUSE., 2016)
A scholarly reprint edition of the ""lost"" queer modernist novel A Scarlet Pansy by Robert Scully based on the original 1932 Faro edition.